PENGARUH PERTUMBUHAN PENJUALAN, PROFITABILITAS, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Maya Ayu Lokassati; Rina Hartanti (EBID: Ekonomi Bisnis Digital, 2024)
This study aims to determine the relationship between Sales Growth, Capital Structure, Profitability also Liquidity on Company Value in mining sector companies written on the IDX for the period 2020 to 2022. This study uses a purposive sampling technique, with a sample of 16 companies from 63 companies. mining sector for the 2020-2022 period. So the research data used was 48. The analysis techniques used in this study were descriptive statistics, panel data regression, t test (partial), also hypothesis testing. According on the research results, the variables Sales Growth, Profitability, Capital Structure and Liquidity have no effect also are not significant on Company velue.